Composite lithium negative electrode, method for preparing same, and battery
Patent Information
- Application Number
- CN202310907723.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-07-24
AI Technical Summary
尽管该策略都很大程度优化了固态电解质和锂金属的界面稳定性,但是仍然存在很大的局限性,包括用来构建离子导电通路的LPS固态电解质与锂金属之间的不相容性以及无法承受高电流密度和高面容量,不足以满足商业应用
[0032](1)本发明的制备方法简单易行,可以集成到现有的全固态锂金属电池制造工艺上,实现规模化生产。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery anode technology, specifically to a composite lithium anode, its preparation method, and a battery. Background Technology
[0002] All-solid-state lithium metal batteries have become one of the main research and development routes for next-generation energy storage systems due to their high energy density and high safety. Furthermore, the use of thermally stable solid electrolytes instead of flammable liquid electrolytes eliminates the risks of electrolyte leakage, combustion, and explosion, significantly improving their safety performance. Sulfide-based all-solid-state lithium metal batteries hold promise for achieving even higher energy densities to meet more specialized and demanding applications. However, interfacial issues such as side reactions, high interfacial resistance, and lithium dendrite growth severely limit the rate performance and cycle life of sulfide-based all-solid-state lithium metal batteries.
[0003] In typical sulfide electrolytes, high-valence cations in the anion clusters, such as P 5+ 、Ge 4+ Sn 4+ Sulfide solid-state electrolytes readily react with lithium metal to form highly electronically conductive interfacial phases, leading to increased ohmic resistance and decreased coulombic efficiency. Furthermore, unlike liquid electrolytes that can directly wet the electrodes, the solid / solid contact in sulfide-based all-solid-state batteries is not ideal, further increasing the contact resistance at the negative electrode interface. Although sulfide solid-state electrolytes exhibit better interfacial contact than oxide solid-state electrolytes, during lithium stripping / plating, increased contact loss at the sulfide-lithium negative electrode interface increases local current density, accelerates lithium dendrite growth, and ultimately punctures the solid electrolyte, causing serious safety issues. Therefore, to address these problems, researchers have proposed various strategies and made some progress, including adjusting the composition of sulfide solid-state electrolytes, using alloy layers, and constructing artificial SEI films. While these strategies can alleviate interfacial problems to some extent and promote uniform lithium metal deposition at the interface, under high current densities, they can easily cause a "point effect," disrupting the dendrite-free, flat growth trend of lithium metal and causing it to grow in a dendritic pattern, eventually puncturing the solid electrolyte and leading to a short circuit.
[0004] A promising approach is to construct a three-dimensional ion / electron hybrid conductive interface protective layer. This layer can facilitate rapid lithium-ion transport at the interface, effectively remove lithium deposits from the interface, induce uniform lithium metal deposition within the interface layer, and effectively suppress lithium dendrite growth, thereby improving the electrochemical performance of the battery. Although this strategy significantly optimizes the interfacial stability between the solid electrolyte and lithium metal, it still has significant limitations, including the incompatibility between the LPS solid electrolyte used to construct the ion-conducting pathway and lithium metal, and its inability to withstand high current densities and high areal capacities, making it insufficient for commercial applications. Summary of the Invention
[0005] This invention addresses the problems in existing technologies by disclosing a lithium metal-containing composite layer and its preparation method. The lithium metal-containing composite layer obtained by this invention forms an interface layer on the surface of the lithium-containing layer. This interface layer can also isolate side reactions between the electrolyte and the lithium metal-containing negative electrode. The resulting lithium metal-containing composite layer also exhibits higher ionic conductivity and reduces the formation of lithium dendrites in the battery, thereby improving the battery's electrical and safety performance. Furthermore, the preparation method of this invention is simple and easy to implement, and can be integrated into existing all-solid-state lithium metal battery manufacturing processes for large-scale production.
[0006] This invention is achieved through the following technical solution:
[0007] This invention provides a method for preparing a lithium metal-containing composite layer. The method includes: mixing soft carbon and Li3N (lithium nitride) to form a precursor interface layer; combining the obtained precursor interface layer with a lithium-containing layer and subjecting the mixture to pressure and heat treatment to obtain the lithium metal-containing composite layer. In this method, under pressure, the soft carbon promotes the rapid transformation of all α-phase in Li3N into β-phase. The β-phase Li3N is beneficial for improving the ionic conductivity of the lithium metal-containing composite layer while reducing the electronic conductivity. The higher ion diffusion rate can promote the diffusion of Li3N under the driving force of concentration. + Diffusion occurs into the lithium-containing metal composite layer, and the lower electronic conductivity can increase the potential difference of the lithium-containing metal composite layer, thus benefiting Li... + Diffusion provides a greater driving force, while thermal insulation of the precursor interface layer and the lithium-containing layer maintains the stability of the transformed β phase in Li3N. Furthermore, it facilitates the rapid reaction between the soft carbon in the precursor interface layer and the metallic lithium in the lithium-containing layer to form LiC6. LiC6 possesses excellent ionic conductivity, further enhancing the ion diffusion rate of the lithium-containing metal composite layer. A higher ion diffusion rate can promote Li3N under the driving force of concentration. +Rapid transport via the Li3N ion conductive pathway induces the nucleation and growth of lithium metal around Li3N particles within the soft carbon-Li3N interface layer, effectively reducing local current density, homogenizing lithium ion flux, and preventing the formation and growth of lithium dendrites.
[0008] As a further embodiment, the pressure per unit area of the pressurized area shall not be less than 875 MPa.
[0009] As a further embodiment, the pressure per unit area under pressurization is 875 MPa-1000 MPa; the temperature of the heat preservation treatment is 45℃-65℃, and the heat preservation treatment time is 11h-13h. Within this range, the prepared lithium-metal composite layer exhibits better electrical and safety performance.
[0010] As a further embodiment, the preparation method also includes mixing soft carbon and Li3N and then adding a binder. This binder is used to connect the soft carbon and Li3N, and also facilitates the connection between the interface layer and the lithium-containing layer.
[0011] As a further embodiment, the compounding method includes pressing. However, the compounding method in this invention is not limited to pressing.
[0012] As a further embodiment, the preparation method includes a preparation environment in an inert gas atmosphere.
[0013] As a further embodiment, the inert gas includes one of argon, nitrogen, helium, krypton, and xenon.
[0014] The present invention provides a lithium metal composite layer, wherein the lithium metal composite layer includes a lithium-containing layer, and an interface layer is disposed on the surface of the lithium-containing layer. The interface layer includes soft carbon, β-Li3N (lithium nitride with only β phase), and LiC6 (lithium hexacarbonide).
[0015] The above-described design of this invention: soft carbon promotes the rapid transformation of all α-phases in Li3N into β-phase. The β-phase Li3N in the interface layer is beneficial for improving the ionic conductivity of the lithium-containing metal composite layer, while also reducing the electronic conductivity of the interface layer. The higher ion diffusion rate can promote the diffusion of Li3N under the driving force of concentration. + Diffusion occurs into the lithium-containing metal composite layer, and the lower electronic conductivity can increase the potential difference of the lithium-containing metal composite layer, thus benefiting Li... + Diffusion provides a greater driving force; LiC6 has good ionic conductivity, which can further enhance the ion diffusion rate of lithium-containing metal composite layers. A higher ion diffusion rate can promote the diffusion of Li under the driving force of concentration. +Rapidly transported through the Li₃N (lithium nitride) ion conduction paths, inducing the nucleation and growth of lithium metal around Li₃N particles inside the soft carbon-Li₃N interfacial layer, which effectively reduces the local current density, homogenizes the lithium ion flux, and avoids the formation and growth of lithium dendrites.
[0016] The lithium-containing layer in the present invention includes a single lithium metal layer or a mixed layer of lithium metal and other substances.
[0017] As a further solution, the raw materials of the interfacial layer include soft carbon and Li₃N (lithium nitride with α phase and β phase); the lithium-containing layer comprises metallic lithium. The arrangement between carbon atoms of soft carbon can be arbitrarily rotated or translated, thereby changing the interlayer spacing and layer plane of soft carbon, which is more conducive to promoting the rapid transformation of all α phases in Li₃N into β phases.
[0018] As a further solution, the mass ratio of the soft carbon to Li₃N is soft carbon: Li₃N = 100%-X%: X% (0<X≤20). If the doping amount of Li₃N is higher than 20%, more Li₃N particles will be in contact with each other, which is not conducive to the improvement of the ionic conductivity of the composite interfacial layer and Li + rapid transport, thereby affecting the electrochemical performance of the battery. This is mainly due to the high Young's modulus and large particle size (5μm-8μm) of Li₃N particles. The contact between particles only by cold pressing is not tight, and there is a large grain boundary resistance, which seriously affects the improvement of the ionic conductivity of the composite interfacial layer and Li + rapid transport.
[0019] As a still further solution, the mass ratio of the soft carbon to Li₃N is soft carbon: Li₃N = 100%-X%: X% (7≤X≤13). When the doping amount of Li₃N is in the range of 7%-13%, on the one hand, the ionic conductivity of the composite interfacial layer can be significantly improved, which is beneficial to Li + rapid transport, thereby improving the electrochemical performance of the battery; on the other hand, the mutual contact between Li₃N particles can be reduced, which is conducive to the improvement of the ionic conductivity of the composite interfacial layer and Li + rapid transport, thereby improving the electrochemical performance of the battery.
[0020] As a further solution, the soft carbon includes one or more of petroleum coke, needle coke, carbon fiber, coke, and carbon microspheres.
[0021] As a further solution, the raw materials of the interfacial layer further include a binder.
[0022] As a further embodiment, the binder includes one or more of PTFE (polytetrafluoroethylene), polyvinylidene fluoride, styrene-butadiene rubber, alginate, polyacrylonitrile, and sodium carboxymethyl cellulose. PTFE has good adhesion and can form an elastic network structure in the electrode matrix. In this structure, the active materials not only have good contact with each other, which is conducive to electron conduction, but also resist the expansion and contraction caused by electrode charging and discharging, thereby improving the discharge performance and storage life of the lithium battery.
[0023] As a further embodiment, the added mass of the binder is 4%-6% of the total mass of soft carbon and Li3N.
[0024] As a further option, the thickness of the interface layer is 30μm-100μm. In batteries, we generally set the interface layer to a more suitable thickness range of 30μm-100μm.
[0025] As a further improvement, the thickness of the interface layer is 30μm-50μm. An interface layer with a thickness within this range is beneficial for improving the ion transport rate of the battery and for increasing the overall energy density of the battery.
[0026] This invention provides a negative electrode, positive electrode, or separator having the aforementioned lithium metal-containing composite layer. The lithium metal-containing composite layer of this invention is particularly suitable for use in negative electrodes to form lithium metal-containing negative electrodes. These negative electrodes not only suppress the formation of lithium dendrites in the negative electrode but also enhance ion conductivity, thereby improving battery safety and electrical performance. The formed lithium metal-containing negative electrodes include lithium metal negative electrodes and pre-lithiated negative electrodes. Specifically, pre-lithiated negative electrodes include pre-lithiated graphite, pre-lithiated silicon-carbon, and pre-lithiated silicon-oxygen, etc. When the lithium metal-containing composite layer of this invention is used in a positive electrode, it not only serves as a lithium replenishment material but also promotes ion conductivity in the positive electrode. When the lithium metal-containing composite layer is used in a separator, it helps to improve the ion conduction rate.
[0027] The present invention also provides a battery or digital battery having the aforementioned negative electrode, positive electrode, or separator, which can be used in 3C products, including but not limited to computers, tablets, mice, mobile phones, digital cameras, Walkmans, electronic dictionaries, digital audio players, smartwatches, MP3 players, MP4 players, radios, and Bluetooth headsets.
[0028] As a further option, the battery includes a sulfide solid electrolyte battery or an all-solid-state lithium metal battery.
[0029] The present invention also provides an electrochemical device having the aforementioned negative electrode, positive electrode, or separator, which can be used in end consumer products. The end consumer products claimed include, but are not limited to, mobile phones, laptops, pen input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, and portable printers.
[0030] The present invention also provides an electrochemical device having the aforementioned negative electrode, positive electrode, or separator, which can be used in electrical equipment, including large and small electrical equipment. Small electrical equipment includes consumer products, wearable electronic devices, or portable electronic devices; large electrical equipment includes transportation equipment. Transportation equipment includes, but is not limited to, vehicles such as automobiles, motorcycles, electric bicycles, buses, subways, high-speed trains, airplanes, and ships; wearable electronic devices or portable electronic devices include, but are not limited to, headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, drones, motors, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors. The negative electrode, positive electrode, or separator of the present invention is used in an electrochemical device, which can be housed in an electrical device in the form of an electrochemical device. Typically, the electrochemical device includes a battery pack or / multiple battery modules or / single battery module or / single cell and a management system for controlling them.
[0031] The features and beneficial effects of this invention are as follows:
[0032] (1) The preparation method of the present invention is simple and easy to implement, and can be integrated into the existing all-solid-state lithium metal battery manufacturing process to achieve large-scale production.
[0033] (2) The lithium metal composite layer prepared by the method of the present invention has higher ionic conductivity, can reduce the formation of lithium dendrites, and can isolate the side reaction between the electrolyte and the lithium metal negative electrode, thereby improving the electrical performance and safety performance of the battery. Attached Figure Description
[0034] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0035] Figure 1 The XRD patterns of the embodiments and comparative examples of this invention before and after lithiation are shown below. Figure 1a is the XRD pattern of the interface layer before lithiation. Figure 1 b is the XRD pattern of the interface layer after lithiation. Figure 1 c is the XRD pattern of the phase transition of Li3N in the interface layer by soft carbon.
[0036] Figure 2 The images shown are SEM and EDS diagrams of the interface layer in the embodiments and comparative examples of the present invention. Figure 2 a is a SEM image of the SC interface layer at a magnification of 20 μm. Figure 2 b is a SEM image of the SC interface layer at a magnification of 10 μm. Figure 2 c is a SEM image of the SC-10% Li3N interface layer at a magnification of 20 μm. Figure 2 d is a SEM image of the SC-10% Li3N interface layer at a magnification of 10 μm. Figure 2 e is the EDS elemental distribution of the SC-10% Li3N interface layer at a magnification of 20 μm. Figure 2 f is the EDS elemental distribution diagram of the SC-10%Li3N interface layer at a magnification of 20μm.
[0037] Figure 3 This is a model and schematic diagram of the internal structure of an electronic blocking battery.
[0038] Figure 4 The electrical properties of the interface layer in the embodiments and comparative examples of the present invention are shown below. Figure 4 a is the AC impedance at the initial stage of lithiation of the interface layer. Figure 4 b represents the AC impedance after complete lithiation of the interface layer. Figure 4 c represents the lithium-ion diffusion coefficient of the interface layer versus voltage curve.
[0039] Figure 5 The images shown are SEM and EDS images of lithium deposition before and after at different current densities in the embodiments and comparative examples of the present invention. Figure 5 a is a SEM image of the SC-Li anode before lithium deposition at a magnification of 20 μm. Figure 5 b is a SEM image of the SC-Li anode before lithium deposition at a magnification of 10 μm. Figure 5 c is a SEM image of the SC-Li anode after lithium deposition at a magnification of 20 μm. Figure 5 d is a SEM image of the SC-Li anode after lithium deposition at a magnification of 10 μm. Figure 5 e is a SEM image at 20 μm magnification before SC-10% Li3N-Li anode deposition. Figure 5 f is a SEM image at 10 μm magnification before SC-10% Li3N-Li anode deposition. Figure 5 g is the EDS elemental distribution at 10 μm magnification before SC-10% Li3N-Li anode deposition. Figure 5 h is the EDS elemental distribution at 10 μm magnification before SC-10% Li3N-Li anode deposition. Figure 5 i is the EDS elemental distribution at 10 μm magnification before SC-10% Li3N-Li anode deposition. Figure 5 j is the EDS elemental distribution map at 10 μm magnification before SC-10% Li3N-Li anode deposition. Figure 5 k is a SEM image of SC-10% Li3N-Li anode deposited at a magnification of 20 μm. Figure 5 Image l is a SEM image at 10 μm magnification after SC-10% Li3N-Li anode deposition. Figure 5 m is the EDS elemental distribution map at 10 μm magnification after SC-10% Li3N-Li anode deposition. Figure 5 n is the EDS elemental distribution map after SC-10% Li3N-Li anode deposition at a magnification of 10 μm. Figure 5 o is the EDS elemental distribution map at 10 μm magnification after SC-10% Li3N-Li anode deposition. Figure 5 p is the EDS elemental distribution map at 10 μm magnification after SC-10% Li3N-Li anode deposition.
[0040] Figure 6 Schematic diagram of the lithium deposition mechanism of the interface layer in the embodiments and comparative examples of the present invention, wherein Figure 6 a is a schematic diagram of the lithium deposition mechanism at the SC interface layer. Figure 6 b is a schematic diagram of the lithium deposition mechanism of the SC-10%Li3N interface layer.
[0041] Figure 7 These are the simulation results of the embodiment and the comparative phase field simulation of the present invention, wherein... Figure 7 a represents the lithium morphology after deposition in the SC-Li3N interface layer. Figure 7 b represents the simulated distribution of lithium ion concentration over time in the SC-Li3N interface layer. Figure 7 c represents the lithium morphology after deposition in the SC interface layer. Figure 7 d represents the simulated distribution of lithium ion concentration over time in the SC interface layer.
[0042] Figure 8 The Tafel curves of lithium symmetric batteries assembled using the interface layers of the embodiments and comparative examples of the present invention are shown at -5°C.
[0043] Figure 9 The electrical performance test results of the embodiments and comparative examples of the present invention are shown below. Figure 9 a represents the current density of a lithium-ion symmetric battery with different interface layers. Figure 9b is a magnified view of the current density when a voltage drop occurs in Li metal. Figure 9 c is a magnified view of the current density when a voltage drop occurs at the SC interface. Figure 9 d is a locally magnified view of the current density when a voltage drop occurs at the SC-10%Li3N interface layer. Figure 9 e is a locally magnified view of the current density when a voltage drop occurs at the SC-20%Li3N interface layer. Figure 9 f represents the cycle performance of lithium-symmetric batteries with different interface layers.
[0044] Figure 10 For high-rate and long-cycle sulfide all-solid-state lithium metal batteries, among which Figure 10 a represents the charge-discharge curves of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery at different rates. Figure 10 b represents the rate performance of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery. Figure 10 c is a comparison of SC-10%Li3N-Li with other literature. Figure 10 d is an LZO@LCO / LPSCl / SC-x%Li3N-Li (x% = 0wt%, 10wt%, 20wt%) all-solid-state lithium metal battery with a capacity of 0.2mAh cm⁻¹. -2 Rate performance under areal capacity Figure 10 e is an LZO@LCO / LPSCl / SC-x%Li3N-Li (x% = 0wt%, 10wt%, 20wt%) all-solid-state lithium metal battery with a capacity of 0.2mAh cm⁻¹. -2 Cyclic performance under areal capacity Figure 10 f is the charge-discharge curve of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery at 30C.
[0045] Figure 11 For high current density and long cycle life sulfide all-solid-state lithium metal batteries, among which, Figure 11 a represents the charge-discharge curves of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery at different rates. Figure 11 b represents the rate performance of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery. Figure 11 c is a comparison of the current density of the SC-10%Li3N of this invention with that of other literature. Figure 11 d represents the cycle performance of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery at 15C.
[0046] Figure 12It is a high-area-capacity sulfide all-solid-state lithium metal battery, in which Figure 12 a is a surface capacity of 3mAh cm -2 Charge-discharge curves of LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal batteries at 1C. Figure 12 b is a surface capacity of 3mAh cm -2 Cycle performance of LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery Figure 12 c is the surface capacity of 3mAh cm -2 Rate performance of LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery, Figure 12 d is a surface capacity of 3mAh cm -2 Charge-discharge curves of LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery at different rates; Figure 12 e represents the charge-discharge curves of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery at different areal capacities. Figure 12 f is a comparison of the areal capacity of this work (SC-10%Li3N-Li) with other literature; Figure 12 g is a surface capacity of 7mAh cm -2 Charge-discharge curves of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery at 0.1C. Figure 12 h is a surface capacity of 7mAh cm -2 Cycle performance of LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery. Detailed Implementation
[0047] To facilitate understanding of the lithium metal composite layer and its preparation method of the present invention, a more comprehensive description of the lithium metal composite layer and its preparation method of the present invention will be given below, and embodiments of the present invention will be provided, but this does not limit the scope of the present invention.
[0048] In this case, the lithium-metal composite layer prepared in the examples and comparative examples is used as an example of a negative electrode sheet to further study the improvement effect on the electrical performance and safety performance of the battery when the lithium-metal composite layer of the present invention is used as a negative electrode sheet. In the examples and comparative examples of the present invention, the lithium-containing layer in the lithium-metal composite layer is lithium metal. In the examples and comparative examples of the present invention, coke in soft carbon is used as an example for research; in the following text of the present invention, SC indicates the coke material used in the examples.
[0049] Example 1:
[0050] Preparation of the SC-10%Li3N precursor interface layer: First, in an argon-filled glove box, SC:Li3N was weighed according to a mass ratio of 90%:10%. Then, 5% of the total mass of SC and Li3N PTFE binder was added. The two materials were completely bonded together by continuous stirring and pressing. Next, it was rolled to a thickness of 30μm-100μm using a heated roller press. In Example 1, the rolled thickness was 30μm, thus preparing the SC-10%Li3N precursor interface layer. Finally, it was cut into 10mm diameter discs for later use. The SC-10%Li3N precursor interface layer and Li metal were pressed together under a pressure of 7t (875MPa) per unit area and placed in an oven at 55°C for 12 hours to allow for full lithiation. The lithium anode SC-10%Li3N-Li (i.e., the interface layer of this invention) was obtained.
[0051] Example 2: Preparation of SC-20%Li3N precursor interface layer: First, in an argon-filled glove box, SC:Li3N was weighed according to a mass ratio of 80%:20%. Then, 5% of PTFE binder (based on the total mass of SC and Li3N) was added. The two materials were completely bonded together by continuous stirring and pressing. Next, it was rolled to a thickness of 30μm-100μm using a heated roller press. In this Example 2, the rolled thickness was 30μm, thus preparing the SC-20%Li3N precursor interface layer. Finally, it was cut into 10mm diameter discs for later use. The SC-20%Li3N precursor interface layer and Li metal were pressed together under a pressure of 7t (875MPa) per unit area and placed in an oven at 55℃ for 12 hours to allow for complete lithiation, obtaining the lithium anode SC-20%Li3N-Li.
[0052] Comparative Example 1:
[0053] No interface layer, negative electrode is a metallic lithium sheet.
[0054] Comparative Example 2:
[0055] Preparation of the SC interface layer (soft carbon interface layer): First, in an argon-filled glove box, 5% (by weight) PTFE binder (based on the mass of soft carbon) was added to SC. The two materials were then bonded together completely by continuous stirring and pressing. Next, a heated roller press was used to roll the layer to a thickness of 30 μm-100 μm. In Comparative Example 2, the rolled thickness was 30 μm, thus preparing the SC interface layer. Finally, it was cut into 10 mm diameter discs for later use. The SC interface layer and Li metal were pressed together under a pressure of 7t (875 MPa) per unit area and then placed in an oven at 55°C for 12 hours to allow for complete lithiation, obtaining the lithium anode SC-Li.
[0056] We will also obtain the preparation of LCO positive electrode composite electrodes for batteries by placing different lithium anodes into them: The LCO (lithium cobalt oxide) positive electrode materials used in this experiment are all coated with lithium zirconate oxide (LiZrO2). The specific preparation process is as follows: First, in a glove box filled with argon gas, 0.10043g of zirconium n-propoxide (C 12 H 28 In a glass bottle, 5 mL of isopropanol (C3H8O) solvent was added and stirred for a period of time to form a clear and transparent solution. Then, 91.94 μL of lithium methoxide (CH3OLi) was added and stirred thoroughly. Next, 2 g of LCO was added, and the mixture was heated and stirred at 60 °C for 12 h. The solvent was evaporated to dryness to obtain a black precursor. Finally, the black precursor was placed in an alumina crucible and sintered at 400 °C for 2 h (heating rate 5 °C / min) to obtain the LZO@LCO product. The LZO@LCO:LPSCl:VGCF was weighed according to a mass ratio of LZO:LCO:LPSCl:VGCF = 50:45:5, and then thoroughly mixed under appropriate force to prepare the LCO positive electrode composite electrode. Here, LZO represents lithium zirconate, LPSCl (Li6PS5Cl) represents lithium phosphide sulfide chloride, and VGCF (carbon fiber) represents carbon fiber.
[0057] We also obtained the battery and conducted electrical performance tests.
[0058] (1) All electrochemical data in this experiment were obtained by assembling sulfide all-solid-state lithium batteries using a Swagelok battery mold with a diameter of 10 mm. The specific battery assembly process is as follows: First, in a glove box filled with argon gas containing <0.1 ppm water and <0.1 ppm oxygen, 80 mg of Li6PS5Cl (LPSCl) solid electrolyte was weighed and carefully placed into a self-made battery mold. A pressure of 1 t (~125 MPa) was applied and pressed for 1 min to form a flat surface. Then, the pre-prepared LCO cathode powder (LZO@LCO:LPSCl:VGCF=60:35:5) was evenly sprinkled on the surface of the electrolyte and a pressure of 4 t (~500 MPa) was applied and pressed for 1 min. Then, a pre-prepared 30μm SC-Li3N precursor interface layer and a 20μm (or 50μm) lithium sheet were placed on the other side of LPSCl and pressed together for 1 minute under a pressure of 7t (~875MPa). Finally, the pressure was reduced to 3t (~375MPa) and the screws were tightened in preparation for the next test. Figure 3 This is a model of an assembled sulfide all-solid-state battery and its internal structure diagram.
[0059] (2) The assembly of the symmetrical battery also uses a Swagelok battery mold with a diameter of 10 mm. The specific battery assembly process is as follows: First, in a glove box filled with argon gas containing <0.1 ppm water and <0.1 ppm oxygen, 80 mg of Li6PS5Cl solid electrolyte is weighed and carefully placed into the self-made battery mold. A pressure of 4 t (~500 MPa) is applied and pressed for 1 min to form a flat plane. Then, a pre-prepared 30 μm SC-Li3N precursor interface layer and a 20 μm (or 50 μm) lithium sheet (when 0.2-0.5 mAh / cm²) are placed on the upper and lower sides of the LPS5Cl respectively. 2 The area capacity uses a 20μm lithium chip, with a capacity of 3mAh / cm². 2 -15mAh / cm 2 The area capacity was measured using 50μm lithium sheets, which were pressed together for 1 minute under a pressure of 7t (~875MPa). Finally, the pressure was reduced to 3t (~375MPa) and the screws were tightened in preparation for the next test.
[0060] (3) The AC impedance method involves applying small-amplitude sinusoidal voltage (or current) perturbation signals of different frequencies to a measurement system in equilibrium. By analyzing the frequency signals of the system's response, the impedance of the system under study in different frequency ranges can be inferred. Based on the measured impedance spectrum, the ionic conductivity of the sulfide solid electrolyte or interface layer can be calculated, and the electrode process kinetics can also be studied.
[0061] The AC impedance measurements in this paper were performed on a Zennium Pro electrochemical workstation. The frequency range was set to 1 Hz to 8 MHz, and the voltage amplitude was set to 5 mV.
[0062] (4) Galvanostatic charge / discharge measurement is a commonly used electrochemical testing technique that can effectively measure the performance of electrochemical materials.
[0063] (5) Critical Current Density Test: The assembled Li / SC-Li3N / LPSCl / SC-Li3N / Li symmetric battery was tested for critical current density using the CT3001A Blue Battery Testing System. The entire test was conducted using a constant capacity method, with an areal capacity of 0.25 mAh cm⁻¹. -2 The initial and final current densities are 0.25 mA cm⁻¹, respectively. -2 and 20mA cm -2 The circuit was cyclic for 5 cycles at each current density, and the test temperature was 55℃.
[0064] (6) Cycle stability test: The assembled Li / SC-Li3N / LPSCl / SC-Li3N / Li symmetric cells and LCO / LPSCl / SC-Li3N / Li full cells were subjected to constant current charge-discharge tests on the CT3001A Blue Electric Test System to study the impact of interface modification on battery cycle stability, thereby evaluating the effectiveness of interface modification. The lithium symmetric cells were tested at 2mA cm⁻¹. -2 Current density and 2mAh cm -2 The tests were conducted at the areal capacity. Full cell testing was performed at 0.2 mAh cm⁻¹. -2 (6.0mA cm -2 ), 0.5mAh cm -2 (7.5mA cm -2 ), 3mAh cm -2 (3.0mA cm -2 ), 5mAhcm -2 (0.5mA cm -2 ), 7mAh cm -2 (0.7mA cm -2 ), 10mAh cm -2 (1.0mA cm -2 ), 15mAh cm -2 (1.5mA cm -2 The tests were conducted at different areal capacities (current densities), with a voltage range of 2.5V-4.2V and a test temperature of 55℃.
[0065] (7) Rate Performance Testing: The assembled LCO / LPSCl / SC-Li3N / Li full cells were subjected to constant current charge-discharge tests on a CT3001A blue battery testing system to study the impact of interface modification on the battery rate performance, thereby evaluating the effectiveness of interface modification. (The test was conducted on cells with an areal capacity of 0.2 mAh cm⁻¹.) -2 Under the test conditions, the current density was 0.2 mA cm⁻¹. -2 0.4mA cm -2 1.0mA cm -2 2.0mA cm -2 3.0mA cm -2 4.0mA cm -2 5.0mA cm -2 6.0mAcm -2 The surface capacity is 0.5mAh cm. -2 Under the test conditions, the current density was 0.5 mA cm⁻¹. -2 1.0mA cm -2 2.5mA cm -25.0mA cm -2 7.5mA cm -2 ; with a surface capacity of 3mAh cm -2 Under the test conditions, the current density was 0.3 mA cm⁻¹. -2 0.6mA cm -2 1.5mAcm -2 3.0mA cm -2 The circuit was cyclic for 5 cycles at each current density, with a voltage range of 2.5V to 4.2V, and a test temperature of 55℃.
[0066] (8) Potentiostatic intermittent titration technique (PITT): A measurement method that involves instantaneously changing and maintaining a constant electrode potential while recording the change in current over time. It is commonly used in lithium batteries to measure the diffusion coefficient of lithium in the electrode. This paper uses PITT to measure the lithium-ion diffusion coefficient of SC-Li3N interface layers with different proportions, thereby determining the optimal proportion of Li3N doping.
[0067] The lithium-ion diffusion coefficient of the SC-Li3N interface layer can be calculated using the formula relating the diffusion coefficient (D) to the current (i):
[0068]
[0069] In the formula, D is the diffusion coefficient, i is the current, and L is the electrode thickness.
[0070] The PITT test in this paper was performed on the CT3001A blue electric current test system. First, the open circuit potential was increased by 0.1 mA cm⁻¹. -2 The current density was used to start discharging until the potential reached 0.2V. Then, the potential was instantaneously reduced by 0.02V and maintained for 30 minutes. After that, the potential excitation was removed and a 5-minute relaxation time was allowed until the potential reached 0V. The test temperature was 55℃.
[0071] (9) Tafel polarization curves are often used to analyze the lithium deposition exchange current density. This paper presents a Li / SC-Li3N / LPSCl / SC-Li3N / Li symmetric cell, tested on a Zennium Pro electrochemical workstation at a scan rate of 0.5 mV / s, a voltage range of -0.1 V to 0.1 V, and a test temperature of -5 °C. The lithium deposition exchange current density is obtained by fitting the obtained Tafel curves. The intersection of the fitted lines of the linear portions of the anodic and cathodic polarization curves represents the lithium deposition exchange current density, thus evaluating the effect of interface modification on improving the electrode reaction rate. Verification results analysis:
[0072] Table 1. Ionic conductivity of embodiments of the present invention under different heat preservation times.
[0073]
[0074] Table 2 Comparison of rate capability, current density, and cycle count of all-solid-state batteries
[0075]
[0076] Table 3 Comparison of the areal capacity of all-solid-state batteries
[0077]
[0078]
[0079] We successfully prepared a lithium-metal composite layer using the method of this invention. Further research was conducted on the application of this lithium-metal composite layer in anode plates. In the method of this invention, the addition of soft carbon and the combined pressure treatment of the precursor interface layer and the lithium-containing layer rapidly transform all the α-phase in Li3N into the β-phase. The β-phase Li3N is beneficial for improving the ionic conductivity of the lithium-metal anode while reducing the electronic conductivity. The higher ion diffusion rate can promote the diffusion of Li3N under the driving force of concentration. + Diffusion occurs towards the lithium-containing metal anode, and the lower electronic conductivity can increase the potential difference at the lithium-containing metal anode, thus benefiting Li... + Diffusion provides a greater driving force. Furthermore, we subject the pressurized interface layer to thermal insulation. This insulation process maintains the stability of the transformed β phase in Li3N and facilitates the rapid reaction between soft carbon and lithium metal to form LiC6. LiC6 exhibits excellent ionic conductivity, further enhancing the ion diffusion rate of the lithium-containing anode. Therefore, the preparation method of this invention forms an interface layer on the surface of the lithium-containing anode. This interface layer also isolates side reactions between the electrolyte and the lithium-containing anode. The resulting lithium-containing anode possesses higher ionic conductivity and reduces the formation of lithium dendrites in the battery, thereby improving the battery's electrical and safety performance.
[0080] A lithium-containing metal anode was prepared. In the method of this invention, to promote the transformation of the α phase to the β phase in Li3N under pressure, it is necessary to increase the rate of α-phase to β-phase transformation and further maintain the stability of the transformed β phase. This is beneficial for improving the ionic conductivity of the lithium anode containing only β-phase Li3N and reducing the formation of lithium dendrites. We achieved rapid transformation of the α phase to the β phase in Li3N through the synergistic effect of soft carbon and pressure during lithiation treatment, thus accelerating the conversion rate. Furthermore, we further maintained the stability of the transformed β phase of Li3N through heat preservation treatment. It is worth noting that in the method of this invention, with the assistance of soft carbon, pressure treatment is required for both the precursor interface layer and the lithium-containing layer to promote the rapid transformation of the α phase to the β phase of Li3N in the precursor interface layer.
[0081] First, to verify the product after lithiation of the SC-X%Li3N (X = 0, 10, 20 wt%) precursor interface layer (where SC represents soft carbon), we characterized the SC-X%Li3N precursor interface layer before and after lithiation using XRD. The results are as follows: Figure 1 .
[0082] Figure 1 a shows the XRD patterns of the interface layer of SC-X%Li3N (X% = 0wt%, 10wt%, 20wt%) precursor before lithiation. When the Li3N addition is 0%, the interface layer consists only of soft carbon. Figure 1 The characteristic peak at 21.3° in SC-10%Li3N is the peak of PE used for air isolation. The characteristic peaks at 22.5°, 27.8°, 32.1°, 46.5°, and 51.2° of SC-10%Li3N and SC-20%Li3N are consistent with the peaks of Li3N. Furthermore, the intensity of the characteristic peaks (2θ values of 22.5°, 27.8°, and 32.1°) gradually increases with the increase of Li3N doping, thus proving that Li3N has been successfully incorporated into SC. In addition, the characteristic peaks at 22.5°, 27.8°, and 46.5° are α-Li3N peaks, and the characteristic peaks at 32.1° and 51.2° are β-Li3N peaks. These characteristic peaks are consistent with the peaks of Li3N, further proving that Li3N contains both α- and β phases. Figure 1b shows the XRD patterns of the SC-X%Li3N (X% = 0, 10, 20 wt%) precursor interface layer after lithiation. When the Li3N addition is 0%, the characteristic peak at 23.5° of the XRD curve (SC-Li) is the LiC6 peak, and the characteristic peak at 35.8° is the Li metal peak, indicating that LiC6 is formed after SC lithiation, and the lithium metal is not completely reacted. The characteristic peaks of the α phase in SC-10%Li3N and SC-20%Li3N all disappeared, with only the β-Li3N peak detected at 32.1°. We believe this is because the method of this invention, through the co-pressurization treatment of the precursor interface layer and the lithium-containing metal layer, completely converts the α phase in Li3N into the β phase. The α-Li3N layers have long, narrow cavities and a very loose structure. In the method of this invention, the lithiation treatment induces the α phase to transform into the β phase through pressure, which is more conducive to improving the ionic conductivity of the battery.
[0083] We further investigated the transformation of the α-phase to the β-phase in Li3N induced by soft carbon in the invented method, and the results are as follows: Figure 1 As shown in c. Figure 1 c shows the XRD patterns of Li3N before and after being held at 7t pressure and 55℃ for 12 hours within a unit area. The characteristic peaks of Li3N after being held at 7t pressure and 55℃ for 12 hours within a unit area are consistent with the peaks of pure Li3N, indicating that pure Li3N does not undergo any phase transformation before and after being held at 7t pressure and 55℃ for 12 hours within a unit area. Therefore, this invention requires the synergistic effect of soft carbon to rapidly induce the transformation of the α phase to the β phase in Li3N.
[0084] Based on this, heat preservation treatment can improve the stability of the β phase in lithiated Li3N. Table 1 shows that at 55℃, increasing the heat preservation time improves the ionic conductivity of the lithium anode. After 12 hours of heat preservation, the ionic conductivity of the lithium anode is three times higher than that after 0.5 hours. Therefore, heat preservation treatment can further maintain the stability of the β phase in lithiated Li3N, thereby maintaining the ionic conductivity of the lithium anode.
[0085] To investigate the distribution of Li3N in the interface layer of the SC-10%Li3N precursor, we characterized its surface morphology using SEM and EDS. Figure 2 a and Figure 2 b is a SEM image of the SC interface layer at different magnifications. It can be seen from the image that the SC is in the form of sheets with varying particle sizes, approximately 8 μm in size. There are large gaps between the particles, and the filaments are PTFE used to bind the SC particles. Figure 2 c and Figure 2 d shows the SEM images of the SC-10%Li3N interface layer at different magnifications. Figure 2 e and Figure 2 f is the EDS elemental distribution of the SC-10% Li3N precursor interface layer at a magnification of 20 μm. From... Figure 2 c and Figure 2 It is difficult to distinguish between Li3N and SC particles in d, making it impossible to determine the distribution of Li3N in SC. Further analysis is needed. Figure 2 e and Figure 2 The distribution of N and C elements in f will be used to differentiate and explain this. From... Figure 2 e and Figure 2 As shown in f, C elements are uniformly distributed throughout the entire precursor interface layer, while N elements are relatively less dispersed around the C elements. This indicates that Li3N (5μm-8μm) particles are mainly distributed on the surface and in the interstices of SC particles, thus forming an ion-conducting pathway within the SC and promoting Li... + Fast transmission.
[0086] We investigated the effect of Li3N doping on improving the interfacial ionic conductivity by assembling an electron-blocking battery. The battery structure is as follows: Figure 3 As shown. In Figure 4 a is the initial AC impedance of the SC-X%Li3N (X% = 0, 10, 20 wt%) precursor interface layer during lithiation, from Figure 4 As can be seen from a, the impedance of the SC-10%Li3N precursor interface layer is the lowest, followed by the SC-20%Li3N precursor interface layer, and the impedance of the SC interface layer is the highest. This indicates that the doping of Li3N can significantly improve the ionic conductivity of the interface layer, and the ionic conductivity shows the following pattern: SC-10%Li3N>SC-20%Li3N>SC. Figure 4 b is the Nyquist curve of the SC-X%Li3N precursor interface layer after complete lithiation at 55℃ and a pressure of 7t (875MPa) per unit area. Figure 4 As shown in b, after complete lithiation, the overall impedance of the interface layer of the SC-X%Li3N precursor decreases, indicating that after complete SC lithiation, soft carbon and lithium metal generate ion-conducting LiC6. Furthermore, under high voltage (875 MPa), the low ionic conductivity Li3N transforms into high ionic conductivity β-Li3N. Therefore, the ion-conducting LiC6 and the high ionic conductivity β-Li3N jointly promote lithium-ion transport, further reducing the impedance of the interface layer and significantly improving its ionic conductivity. The ionic conductivity still exhibits the following pattern: SC-10%Li3N > SC-20%Li3N > SC.
[0087] Figure 4 c is the lithium-ion diffusion coefficient versus voltage curve of the SC-X%Li3N (X% = 0, 10, 20 wt%) precursor interface layer after lithiation. Figure 4 As shown in Figure c, the lithium-ion diffusion coefficient of the lithiated SC-X%Li3N precursor interface layer first increases and then decreases with increasing voltage, exhibiting the following pattern at different voltages: SC-10%Li3N > SC-20%Li3N > SC. This demonstrates that the addition of Li3N improves the lithium-ion diffusion coefficient. + The diffusion rate in the SC lattice accelerates the lithium insertion / deintercalation reaction, thereby increasing the lithium-ion diffusion coefficient of the SC-X%Li3N interface layer.
[0088] To evaluate the lithium deposition behavior of the lithiated SC-X%Li3N (X% = 0 and 10 wt%) precursor interface layer, the SC-X%Li3N (X% = 0 and 10 wt%) interface layer at 3 mA cm⁻¹ was studied by SEM. -2 3mAh cm⁻¹ deposited at current density -2 The cross-sectional morphology before and after lithium deposition. Figure 5 a and Figure 5 b is a cross-sectional SEM image of the SC interface layer before lithium deposition. It can be seen from the image that the SC particles were not in close contact before deposition, and there were many voids. Figure 5 c and Figure 5 d represents the SC interface layer after deposition of 3mAh cm⁻¹ -2 The cross-sectional SEM image of the lithium deposit clearly shows that after lithium deposition, numerous lithium dendrites pierce the LPSCl electrolyte, and a large number of voids remain between the SC particles, lacking lithium metal. This indicates that lithium ions directly gain electrons at the SC / LPSCl interface to form lithium dendrites, which then grow into the LPSCl electrolyte and eventually pierce the solid electrolyte. We believe this is mainly because SC has high electronic conductivity and a low lithium-ion diffusion coefficient. Under high current density, electrons will quickly reach the SC / LPSCl electrolyte interface, and Li... + The inability to replenish the charge leads to localized charge buildup, inducing lithium dendrite formation, which eventually punctures the solid electrolyte, causing a short circuit in the battery. A schematic diagram of the lithium deposition mechanism at the SC interface layer is shown below. Figure 6 As shown in a.
[0089] Figure 5 e and Figure 5 f is a cross-sectional SEM image of the lithiated SC-10%Li3N precursor interface layer before lithium deposition. Figure 5 g- Figure 5 j is the corresponding EDS element distribution plot. From Figure 5 e and Figure 5 Figure f shows a large number of voids within the lithium deposition interface layer, indicating that the contact between lithium particles was not tight before deposition. Figure 5 g- Figure 5In sample j, carbon (C) is observed to be uniformly distributed throughout the cross-sectional area, while nitrogen (N) is relatively less dispersed around the C. P and sulfur (S) are uniformly distributed at the top of the cross-section, corresponding precisely to the LPSCl electrolyte. This demonstrates that a small number of Li3N particles are distributed on the surface and in the interstices of the SC particles, forming an ion-conducting pathway that promotes Li... + Fast transmission. Figure 5 k and Figure 5 l represents the interface layer of the lithiated SC-10%Li3N precursor deposited at a depth of 3 mAh cm⁻¹. -2 SEM image of the cross-section after lithium removal. Figure 5 m- Figure 5 p represents the corresponding EDS element distribution plot. From Figure 5 k and Figure 5 In the study, it was observed that after lithium deposition, the particles within the interface layer were almost fused together, forming a very dense structure without any voids. Furthermore, no lithium metal deposition or lithium dendrites were observed at the SC / LPSCl interface. This indicates that lithium metal was deposited within the gaps within the lithiated SC-10%Li3N precursor interface layer. This significantly increases the deposition sites for lithium metal, effectively reducing local current density and suppressing lithium dendrite formation. Figure 5 m- Figure 5 In p, the distribution of C elements is reflected. Figure 5 The white circle in the lower left corner of the m-image is clearly missing. Combined with the significant decrease in nitrogen content after lithium deposition, it can be inferred that lithium metal may have nucleated and grown around Li3N particles, causing the Li3N particles to be encapsulated by the deposited lithium metal. Therefore, the missing area may represent Li3N particles masked by Li. This is mainly because Li3N doping in the SC interface layer increases the ionic conductivity and ion diffusion rate of the interface layer while decreasing the electronic conductivity. The higher ion diffusion rate can promote Li... + Diffusion occurs towards the lithium anode, and the lower electronic conductivity can increase the potential difference at the lithium anode, thus providing a potential for Li... + Diffusion provides a greater driving force. On the other hand, a Li3N ion-conducting pathway is formed within the interface layer, Li + The lithium ions rapidly transport along the Li3N ion conduction pathway and nucleate and grow around the Li3N particles within the interface layer, thus effectively suppressing the growth of lithium dendrites. A schematic diagram of the lithium deposition mechanism at the interface layer of the lithiated SC-10%Li3N precursor is shown below. Figure 6 As shown in b.
[0090] To further verify the influence of the high diffusion coefficient of Li3N on lithium deposition behavior, we used the phase-field method to simulate the SC and SC-Li3N systems at 5 mA cm⁻¹. -2 The lithium deposition process driven by an applied current. For example... Figure 7As shown, 0μm-5μm represents the lithium-ion concentration (C). Li+ Lithium metal with a concentration (ξ) of 0 and a lithium metal concentration (ξ) of 1. 5μm-35μm is the thickness of the lithiated SC / SC-Li3N precursor interface layer under initial conditions. Li+ Both ξ and 0.35 μm are above the LPSCl solid electrolyte layer. Under initial conditions, C Li+ ξ is 1, and ξ is 0. Based on previous studies, the ion diffusion coefficient of LiC6 is relatively low, approximately 10. -11 cm 2 s -1 The diffusion coefficient of Li3N is relatively high, approximately 10. -8 cm 2 s -1 Therefore, lithium ions can diffuse to the SC-Li3N interface layer more quickly. Furthermore, the electronic conductivity of the lithiated SC-Li3N precursor interface layer is 26 times lower than that of the SC interface layer, resulting in a larger potential difference in the lithiated SC-Li3N precursor interface layer to promote lithium ion diffusion. Therefore, a large amount of Li can be observed throughout the lithium deposition process. + It mainly accumulates around the Li3N particles inside the interface layer of the lithiated SC-Li3N precursor. Figure 7 b), and lithium metal preferentially deposits within the lithiated SC-Li3N precursor interface layer, and grows in a spherical shape around the Li3N particles. Figure 7 a) These spherical lithium atoms effectively prevent lithium from growing into dendritic structures, thus avoiding the formation of lithium dendrites. Conversely, in the SC system, due to the slow diffusion rate of lithium ions, it is difficult for them to diffuse into the SC interface layer where the lithium ion concentration is low, thus a large amount of Li... + It mainly accumulates at the interface layer of the SC / LPSCl electrolyte. Figure 7 d), and directly obtain electrons at the interface to form lithium dendrites ( Figure 7 c) As the deposition time increases, lithium dendrites continuously grow into the interior of the LPSCl electrolyte.
[0091] Figure 8 Tafel curves for lithium-ion symmetric cells assembled using lithiated SC-X%Li3N (X% = 0 and 10 wt%) precursor interface layers are shown at -5 °C. Because a very large current would be generated at 0.05 V at room temperature, causing a short circuit, the entire test was conducted at -5 °C. The results show that the Li anode with the interface layer (SC-10%Li3N-Li) exhibits the highest exchange current density (1.135 mA cm⁻¹). 2 This is because the three-dimensional Li3N ion-conducting pathway enhances the lithium-ion transport rate and increases the number of lithium metal deposition sites. The exchange current density of SC-Li is the second highest (0.381 mA cm⁻¹). -2The bare Li has the lowest exchange current density (0.291 mA cm⁻¹). -2 ).
[0092] To investigate the interfacial stability of LPSCl / Li after optimization using a lithiated SC-X%Li3N (X% = 0, 10, 20 wt%) precursor interface layer, we assembled a Li / SC-X%Li3N / LPSCl / SC-X%Li3N-Li symmetric cell with an areal capacity of 0.25 mAh cm⁻¹. -2 The current density is 0.25 mA cm⁻¹ -2 Up to 20mA cm -2 Critical current density (CCD) tests were conducted with a stepwise increase in current density, while the test temperature was maintained at 55°C. From Figure 9 It can be seen that the interface layer of the lithiated SC-10%Li3N precursor exhibits a maximum CCD of 20 mA cm⁻¹. -2 The lithium symmetry at the interface between the lithiated SC-20%Li3N and the SC precursor is 16 mA cm⁻¹. -2 and 10mA cm -2 A significant voltage drop was observed at the current density ( Figure 9 e and Figure 9 c) while bare Li symmetric cells only reach 3 mA cm⁻¹ -2 A voltage drop occurs at current densities ( Figure 9 (b) This is mainly because LPSCl electrolyte readily undergoes side reactions with Li metal, generating undesirable ionic conductors such as Li3P, leading to increased interfacial resistance. Furthermore, the poor interfacial contact between LPSCl and Li results in uneven lithium metal deposition, increased local current density, and accelerated lithium dendrite growth. Clearly, the LPSCl / Li interface optimized with a lithiated SC-10%Li3N precursor interfacial layer exhibits the best electrochemical stability. This is primarily due to the high lithium-ion diffusion coefficient of the interfacial layer separating the LPSCl electrolyte and Li metal, effectively preventing chemical / electrochemical reactions between them, promoting rapid lithium-ion transport, inducing lithium metal deposition within the interfacial layer, reducing local current density, homogenizing lithium-ion flux, thereby increasing the critical current density and suppressing lithium dendrite growth. Furthermore, the lithiated SC-10%Li3N precursor interface layer exhibits good wettability and the highest ionic conductivity, improving the LPSCl / Li interfacial contact and significantly reducing the LPSCl / Li interfacial resistance. Therefore, the Li / SC-10%Li3N / LPSCl / SC-10%Li3N-Li symmetric cell achieves good interfacial resistance at 20 mA cm⁻¹. -2It exhibits a low polarization voltage of only 0.16V even at ultra-high current densities. While the use of the SC interface layer avoids interfacial side reactions in LPSCl / Li and improves the interfacial contact of LPSCl / Li, it also increases the CCD's current density to 10mA cm⁻¹. -2 However, due to the high electronic conductivity of the SC interface layer, Li + The diffusion rate is relatively slow; at high current densities, electrons will rapidly reach the SC / LPSCl interface, Li + If there is not enough time to replenish the charge, local charge buildup will occur, inducing the formation of lithium dendrites, which will eventually puncture the solid electrolyte and cause the battery to short-circuit.
[0093] In addition, from Figure 9 As can be seen from f, the lithium symmetric battery optimized with the lithiated SC-10%Li3N precursor interface layer exhibits the best cycle stability, achieving stable cycling for over 2000 hours (1000 cycles) with the lowest initial polarization voltage (10 mV) and final polarization voltage (15 mV). Conversely, the polarization voltage of the lithium symmetric battery optimized with the SC interface layer continuously increases, short-circuiting after 798 hours of cycling, with a final polarization voltage as high as 52 mV. This is mainly due to the uneven deposition and stripping of lithium, resulting in dead lithium, which increases the interface resistance, leading to a continuous increase in polarization voltage and ultimately a short circuit. The bare Li symmetric battery, on the other hand, short-circuited after only 3 cycles and exhibited a very high initial polarization voltage (20 mV), furthermore, a micro-short circuit occurred during the first cycle.
[0094] In summary, the lithium-symmetric battery optimized with a lithiated SC-10%Li3N precursor interface layer exhibits the highest critical current density and best cycle stability. Furthermore, the electrochemical performance of different interface layer ratios still follows the order: SC-10%Li3N > SC-20%Li3N > SC > Li. Therefore, optimizing the LPSCl / Li interface with a lithiated SC-10%Li3N precursor interface layer demonstrates the best chemical / electrochemical stability, proving that the lithiated SC-10%Li3N precursor interface layer can effectively stabilize the LPSCl / Li interface, avoid interfacial side reactions, improve interfacial contact, and suppress lithium dendrite growth, thereby significantly improving the battery's electrochemical performance. We further optimized the mass ratio of soft carbon to Li3N to be soft carbon:Li3N = 100% - X%:X% (7 ≤ X ≤ 13).
[0095] Based on this, in order to further verify that when the mass ratio of soft carbon to Li3N in this invention is between 100% and X% (7 ≤ X ≤ 13), we take the SC-10% Li3N interface layer as an example for further analysis.
[0096] To better verify the excellent electrochemical performance of the lithiated SC-10%Li3N precursor interface layer, we conducted various electrochemical tests. The lithiated SC-10%Li3N precursor interface layer exhibits a high exchange current density (1.135 mA cm⁻¹). -2 It possesses good ion conductivity and therefore exhibits good rate performance. Surprisingly, even at an ultra-high rate of 100C, the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery still delivers 56.5 mAh g⁻¹. -1 Specific capacity ( Figure 10 a and Figure 10 b). Compared with the rate performance of solid-state batteries reported in the literature, the Li anode with SC-10%Li3N as the interface layer exhibited an unprecedented maximum charge rate (CFR). Figure 10 c). Furthermore, we compared the rate performance and cycle performance of the lithiated SC-X%Li3N (X% = 0, 10, 20 wt%) precursor interface layer, from... Figure 10 d shows that at 0.2mAh cm -2 Surface capacity and 30C (6mA cm) -2 At high rates, the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery can provide the highest specific capacity (99.6 mAh g). -1 The lithiated SC-20%Li3N and SC precursor interface layer provide a relatively low specific capacity (68.4 mAh g⁻¹). -1 and 63.8mAh g -1 Bare Li offers only the lowest specific capacity (20.1 mAh g⁻¹). -1 This demonstrates that the lithiated SC-10%Li3N precursor interface layer exhibits the best rate performance. Furthermore, the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery performs well at 30C (6mA cm⁻¹). -2 It achieves an ultra-long cycling range of 6000 cycles at a high rate, and still provides 97.8mAh g after 6000 cycles. -1 The specific capacity of the SC-20% Li3N precursor interface layer was significantly higher, with a capacity retention rate of up to 98%. In contrast, the specific capacity of the lithiated SC-20% Li3N precursor interface layer decreased to 13.9 mAh g after 6000 cycles. -1 The capacity retention rate was only 20%, while the specific capacity of the SC interface layer and bare Li almost decreased to zero after 50 and 140 cycles, respectively. This also proves that the lithiated SC-10%Li3N precursor interface layer has better cycling performance. Figure 10 e- Figure 10 (as shown in f).
[0097] In summary, the lithiated SC-10%Li3N precursor interface layer exhibits the best rate performance and cycling performance. This is mainly because the high ionic conductivity, high diffusion coefficient, and low electronic conductivity of Li3N doped into the SC interface layer create a Li3N ion conductive pathway within the interface layer, improving the ionic conductivity and ion diffusion rate while simultaneously reducing the electronic conductivity, thus driving lithium ion transport into the interface layer. Therefore, lithium metal can nucleate and grow around the Li3N particles within the interface layer, significantly reducing the local current density and achieving an ultra-high rate capability of 100C and a cycling performance of 30C (6 mA cm⁻¹). -2 The 6000-lap ultra-long cycle under the condition.
[0098] To further demonstrate the excellent electrochemical performance of the lithiated SC-10%Li3N precursor interface layer at high current densities, we further increased the areal capacity and investigated the performance of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery at 0.5 mAh cm⁻¹. -2 Electrochemical performance at areal capacity. From Figure 11 a and Figure 11 b shows that at 0.5mAh cm -2 At its surface capacity, the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery can reach a maximum of 7.5 mA cm⁻¹. -2 It has a high current density, and can still provide up to 108.2 mAh g at this current density. -1 Compared with the current density of solid-state batteries reported in the literature, the Li anode with the lithiated SC-10%Li3N precursor interface layer exhibited a higher limiting current density, exceeding the level of most current solid-state battery lithium anodes. Figure 10 c). Furthermore, the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery achieved a 7.5 mA cm⁻¹ performance. -2 Achieving 3000 cycles at a high current density (high rate) of (15C), and still providing 86.1mAh g after 6000 cycles. -1 The specific capacity has a capacity retention rate of up to 80%. Figure 11 d). This is mainly attributed to the lithiation-enhanced SC-10%Li3N precursor interface layer separating the LPSCl electrolyte and Li metal, effectively preventing chemical / electrochemical reactions between LPSCl and Li metal, promoting rapid lithium-ion transport, inducing lithium metal deposition within the interface layer, reducing local current density, and homogenizing lithium-ion flux, thereby achieving 7.5 mA cm⁻¹. -2It features high current density and a long cycle life of 3000 cycles.
[0099] from Figure 12 a and Figure 12 As can be seen from b, the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery can achieve a capacity of 3mAh cm⁻¹. -2 High surface capacity and 3mA cm -2 After 350 cycles at high current density, the capacity retention rate is as high as 88.1%, and it can still provide 118.1 mAh g even at 1C. -1 Specific capacity ( Figure 12 c and Figure 12 d). In addition, by Figure 12 As can be seen from e, the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery, even at a 5mAh cm⁻¹, -2 and 10mAh cm -2 It still provides 129.1mAh g at 0.1C. -1 and 124.2mAh g -1 The specific capacity, when the surface capacity increases to 15mAh cm⁻¹ -2 At that time, it can still provide 121mAh g at 0.1C. -1 Specific capacity. To our knowledge, 15mAh cm⁻¹ -2 This is the highest reported areal capacity value for all-solid-state, semi-solid-state, and polymer solid-state lithium metal batteries to date. Figure 12 f). Furthermore, at 7mAh cm⁻¹ -2 At the areal capacity, the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery can also achieve 0.1C (0.7mA cm⁻¹). -2 It achieves a long cycle of 100 cycles, and after 100 cycles, it can still provide 100mAh g. -1 The specific capacity has a capacity retention rate of up to 80%. Figure 12 g and Figure 12 h). Therefore, it can be concluded that the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery can achieve a 15mAh cm⁻¹ capacity. -2 Ultra-high surface capacity and high capacity (7mAh cm) -2 The long cycling test (100 cycles, 80% capacity retention) demonstrates its excellent electrochemical performance and promising application prospects. This also proves once again that the lithiated SC-10%Li3N precursor interface layer can effectively stabilize the LPSCl / Li interface, avoid interfacial side reactions, improve interfacial contact, and inhibit lithium dendrite growth, thereby greatly improving the electrochemical performance of the battery.
[0100] We also used the lithium anode of this invention in an all-solid-state battery and compared its electrical performance with that of existing all-solid-state batteries. The results are shown in Tables 2 and 3. It is evident that the lithium anode obtained in this invention exhibits superior electrical performance in all-solid-state batteries.
[0101] In summary, this work designed a soft carbon-Li3N mixed ionic and electronically conductive interface layer and carried it in situ for lithiation. This not only lithiated SC into LiC6 with good electronic / ionic conductivity, but also successfully converted the mixed-phase Li3N into pure-phase β-Li3N with high ionic conductivity / ionic diffusion coefficient and stability to metallic lithium. This promotes the lithiation of LiC6. + Rapid migration at the interface layer induces uniform deposition of metallic lithium within the interface layer, effectively suppressing lithium dendrite growth and significantly improving the electrochemical performance of the all-solid-state lithium metal battery. A lithium-symmetric battery assembled using a lithiated SC-Li3N precursor interface layer achieves a performance of 0.25 mAh cm⁻¹. -2 It showed 20mA cm -2 The ultra-high critical current density of the LZO@LCO / LPSCl / SC-10%Li3N-Li all-solid-state lithium metal battery at 15C (7.5mA cm⁻¹) is achieved. -2 At ultra-high current density, after 3000 cycles, the capacity retention exceeds 80%. Furthermore, at 3mAh cm⁻¹... -2 Despite its high surface capacity, it can still operate at 1C (3mA cm⁻¹). -2 It maintains a stable capacity retention of up to 88.1% after 350 cycles. It also achieves a 15mAh capacity. -2 The ultra-high areal capacity breaks the current record for solid-state lithium metal batteries. Furthermore, the interface layer proposed in this work provides a feasible and scalable method for optimizing the interface between the sulfide solid electrolyte and the lithium metal anode, paving the way for the practical application of all-solid-state lithium metal batteries.
[0102] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
[0103] References in Tables 2-3:
[0104] [1]Ji X, Hou S, Wang P, et al. Solid-State Electrolyte Design for LithiumDendriteSuppression[J]. Advanced Materials, 2020.
[0105] [2]Xing X,Li Y,Wang S,et al.Graphite-Based Lithium-Free 3D HybridAnodes for HighEnergy Density All-Solid-State Batteries[J].Acs EnergyLetters,2021,6(5):1831-1838.
[0106] [3]Xu R,Fudongji,Xiaofan,Xiulintu,Jiangpingwang,Chunsheng.Interfaceengineering ofsulfide electrolytes for all-solid-state lithium batteries[J].Nano Energy,2018,53.
[0107] [4]Chen Y,Li W,Sun C,et al.Sustained Release-Driven Formation ofUltrastable SEIbetween Li6PS5Cl and Lithium Anode for Sulfide-Based Solid-State Batteries[J].AdvancedEnergy Materials,2021,11(4).
[0108] [5]Cheng Z,Pan H,Li F,et al.Achieving long cycle life for all-solid-state rechargeableLi-I-2battery by a confined dissolution strategy[J].NatureCommunications,2022,13(1).
[0109] [6]Liang J,Li X,Zhao Y,et al.In Situ Li3PS4 Solid-State ElectrolyteProtection Layers forSuperior Long-Life and High-Rate Lithium-Metal Anodes[J].Advanced Materials,2018,30(45).
[0110] [7]Kim C,Kim J,Park J,et al.Ion-Conducting Channel Implanted AnodeMatrix forAll-Solid-State Batteries with High Rate Capability and StableAnode / Solid ElectrolyteInterface[J].Advanced Energy Materials,2021,11(40).
[0111] [8]Lee K,Han S,Lee J,et al.Multifunctional Interface for High-Rateand Long-DurableGarnet-Type Solid Electrolyte in Lithium Metal Batteries[J].Acs Energy Letters,2022,7(1):381-389.
[0112] [9]Wan H,Zhang J,Xia J,et al.F and N Rich Solid Electrolyte forStable All-Solid-StateBattery[J].Advanced Functional Materials,2022,32(15).
[0113]
[10] Zhou L,Zuo T-T,Kwok C Y,et al.High areal capacity,long cycle life4V ceramicall-solid-state Li-ion batteries enabled by chloride solidelectrolytes[J].Nature Energy,2022,7(1):83-93.
[0114]
[11] Peng L,Yu C,Zhang Z,et al.Chlorine-rich lithium argyroditeenabling solid-statebatteries with capabilities of high voltage,high rate,low-temperature and ultralongcyclability[J].Chemical Engineering Journal,2022,430.
[0115]
[12] Tan D H S,Chen Y-T,Yang H,et al.Carbon-free high-loading siliconanodes enabled bysulfide solid electrolytes[J].Science,2021,373(6562):1494-+.
[0116]
[13] Lee Y-G,Fujiki S,Jung C,et al.High-energy long-cycling all-solid-state lithium metalbatteries enabled by silver-carbon composite anodes[J].Nature Energy,2020,5(4):299-308.
[0117]
[14] Liu Y,Lin D,Jin Y,et al.Transforming from planar to three-dimensional lithium withflowable interphase for solid lithium metal batteries[J].Science Advances,2017,3(10).
[0118]
[15] Zhang Z,Chen S,Yao X,et al.Enabling high-areal-capacity all-solid-state lithium-metalbatteries by tri-layer electrolyte architectures[J].Energy Storage Materials,2020,24:714-718.
[16] Zhu G-L,Zhao C-Z,Peng H-J,etal.A Self-Limited Free-Standing Sulfide ElectrolyteThin Film for All-Solid-State Lithium Metal Batteries[J].Advanced Functional Materials,2021,31(32).
[0119]
[17] Santhosha A L,Nazer N,Koerver R,et al.Macroscopic DisplacementReaction ofCopperSulfide in Lithium Solid-State Batteries[J].Advanced EnergyMaterials,2020,10(41).
[0120]
[18] Yan H,Wang H,Wang D,et al.In-situ generated Li2S-C nanocompositeforHigh-Capacity and Long-Life All-Solid-State Lithium Sulfur Batteries withUltrahigh ArealMass Loading[J].Nano Letters,2019.
[0121]
[19] Doerrer C,Capone I,Narayanan S,et al.High Energy Density Single-CrystalNMC / Li6PS5Cl Cathodes for All-Solid-State Lithium-Metal Batteries[J].Acs AppliedMaterials&Interfaces,2021,(31):13.
[0122]
[20] Li X, Liang J, Luo J, et al. High-Performance Li-SeSₓ All-Solid-State Lithium Batteries[J]. Advanced Materials, 2019, 31(17): 1808100.1808101-1808100.1808110.
[0123]
[21] Han X, Wang S, Xu Y, et al. All solid thick oxide cathodes based on low temperature sintering for high energy solid batteries[J]. Energy & Environmental Science, 2021, 14(9): 5044-5056.
[0124] Figure 10 References in c:
[0125] 1. Xu R, Fudong Ji, Xiao Fan, Xiulin Tu, Jiangping Wang, Chunsheng. Interface engineering of sulfide electrolytes for all-solid-state lithium batteries. Nano Energy 2018, 53.
[0126] 2. Ji X, Hou S, Wang P, He X, Nan P, Chen J, et al. Solid-State Electrolyte Design for Lithium Dendrite Suppression. Advanced Materials 2020.
[0127] 3. Wan H, Zhang J, Xia J, Ji X, He X, Liu S, et al. F and N Rich Solid Electrolyte for Stable All-Solid-State Battery. Advanced Functional Materials 2022, 32(15).
[0128] 4.Kim C,Kim J,Park J,Kim J,Lee S,Sun S,et al.Ion-Conducting ChannelImplanted Anode Matrix for All-Solid-State Batteries with High RateCapability and Stable Anode / Solid Electrolyte Interface.Advanced EnergyMaterials 2021,11(40).
[0129] 5.Chen Y,Li W,Sun C,Jin J,Wang Q,Chen X,et al.Sustained Release-Driven Formation of Ultrastable SEI between Li6PS5Cl and Lithium Anode forSulfide-Based Solid-State Batteries.Advanced Energy Materials 2021,11(4).
[0130] 6.Liang J,Li X,Zhao Y,Goncharova LV,Wang G,Adair KR,et al.In SituLi3PS4 Solid-State Electrolyte Protection Layers for Superior Long-Life andHigh-Rate Lithium-Metal Anodes.Advanced Materials 2018,30(45).
[0131] 7.Lee Y-G,Fujiki S,Jung C,Suzuki N,Yashiro N,Omoda R,et al.High-energy long-cycling all-solid-state lithium metal batteries enabled bysilver-carbon composite anodes .Nature Energy 2020,5(4):299-308.
[0132] 8.Tan DHS,Chen Y-T,Yang H,Bao W,Sreenarayanan B,Doux J-M,etal.Carbon-free high-loading silicon anodes enabled by sulfide solidelectrolytes.Science 2021,373(6562):1494.
[0133] 9.Lee K,Han S,Lee J,Lee S,Kim J,Ko Y,et al.Multifunctional Interfacefor High-Rate and Long-Durable Garnet-Type Solid Electrolyte in Lithium MetalBatteries.Acs Energy Letters 2022,7(1):381-389.
[0134] 10.Zhou L,Zuo T-T,Kwok CY,Kim SY,Assoud A,Zhang Q,et al.High arealcapacity,long cycle life 4 V ceramic all-solid-state Li-ion batteries enabledby chloride solid electrolytes.Nature Energy 2022,7(1):83-93.
[0135] 11.Cheng Z,Pan H,Li F,Duan C,Liu H,Zhong H,et al.Achieving long cyclelife for all-solid-state rechargeable Li-I2 battery by a confined dissolutionstrategy.Nature Communications 2022,13(1).
[0136] 12. Peng L, Yu C, Zhang Z, Ren H, Zhang J, He Z, et al. Chlorine-rich lithium argyrodite enabling solid-state batteries with capabilities of high voltage, high rate, low-temperature and ultralong cyclability. Chemical Engineering Journal 2022, 430.
[0137] 13. Ye L, Li X. A dynamic stability design strategy for lithium metal solid state batteries. Nature 2021, 593(7858): 218.
[0138] 14. D.H. Kim et al., Infiltration of solution-processable solid electrolytes into conventional Li-ion-battery electrodes for all-solid-state Li-ion batteries. Nano letters 17, 3013-3020 (2017).
[0139] Figure 11 References in c:
[0140] 1. Xu R, Fudong Ji, Xiao Fan, Xiulin Tu, Jiangping Wang, Chunsheng. Interface engineering of sulfide electrolytes for all-solid-state lithium batteries. Nano Energy 2018, 53.
[0141] 2. Ji X, Hou S, Wang P, He X, Nan P, Chen J, et al. Solid-State Electrolyte Design for Lithium Dendrite Suppression. Advanced Materials 2020.
[0142] 3.Chen Y,Li W,Sun C,Jin J,Wang Q,Chen X,et al.Sustained Release-Driven Formation of Ultrastable SEI between Li6PS5Cl and Lithium Anode forSulfide-Based Solid-State Batteries.Advanced Energy Materials 2021,11(4).
[0143] 4.Cheng Z,Pan H,Li F,Duan C,Liu H,Zhong H,et al.Achieving long cyclelife for all-solid-state rechargeable Li-I2 battery by a confined dissolutionstrategy.Nature Communications 2022,13(1).
[0144] 5.Liang J,Li X,Zhao Y,Goncharova LV,Wang G,Adair KR,et al.In SituLi3PS4 Solid-State Electrolyte Protection Layers for Superior Long-Life andHigh-Rate Lithium-Metal Anodes.Advanced Materials 2018,30(45).
[0145] 6.Kim C,Kim J,Park J,Kim J,Lee S,Sun S,et al.Ion-Conducting ChannelImplanted Anode Matrix for All-Solid-State Batteries with High RateCapability and Stable Anode / Solid Electrolyte Interface.Advanced EnergyMaterials 2021,11(40).
[0146] 7.Lee K,Han S,Lee J,Lee S,Kim J,Ko Y,et al.Multifunctional Interfacefor High-Rate and Long-Durable Garnet-Type Solid Electrolyte in Lithium MetalBatteries.Acs Energy Letters 2022,7(1):381-389.
[0147] 8.Wan H,Zhang J,Xia J,Ji X,He X,Liu S,et al.F and N Rich SolidElectrolyte for Stable All-Solid-State Battery.Advanced Functional Materials2022,32(15).
[0148] 9.Zhou L,Zuo T-T,Kwok CY,Kim SY,Assoud A,Zhang Q,et al.High arealcapacity,long cycle life 4 V ceramic all-solid-state Li-ion batteries enabledby chloride solid electrolytes.Nature Energy 2022,7(1):83-93.
[0149] 10.Peng L,Yu C,Zhang Z,Ren H,Zhang J,He Z,et al.Chlorine-rich lithiumargyrodite enabling solid-state batteries with capabilities of high voltage,high rate,low-temperature and ultralong cyclability.Chemical EngineeringJournal 2022,430.
[0150] 11. Tan DHS, Chen Y-T, Yang H, Bao W, Sreenarayanan B, Doux J-M, et al. Carbon-free high-loading silicon anodes enabled by sulfide solid electrolytes. Science 2021, 373(6562): 1494.
[0151] 12. Lee Y-G, Fujiki S, Jung C, Suzuki N, Yashiro N, Omoda R, et al. High-energy long-cycling all-solid-state lithium metal batteries enabled by silver-carbon composite anodes. Nature Energy 2020, 5(4): 299-308.
[0152] Figure 12 References in f:
[0153] 1. Xu R, Fudong Ji, Xiao Fan, Xiulin Tu, Jiangping Wang, Chunsheng. Interface engineering of sulfide electrolytes for all-solid-state lithium batteries. Nano Energy 2018, 53.
[0154] 2. Ji X, Hou S, Wang P, He X, Nan P, Chen J, et al. Solid-State Electrolyte Design for Lithium Dendrite Suppression. Advanced Materials 2020.
[0155] 3. Wan H, Zhang J, Xia J, Ji X, He X, Liu S, et al. F and N Rich Solid Electrolyte for Stable All-Solid-State Battery. Advanced Functional Materials 2022, 32(15).
[0156] 4.Kim C,Kim J,Park J,Kim J,Lee S,Sun S,et al.Ion-Conducting ChannelImplanted Anode Matrix for All-Solid-State Batteries with High RateCapability and Stable Anode / Solid Electrolyte Interface.Advanced EnergyMaterials 2021,11(40).
[0157] 5.Chen Y,Li W,Sun C,Jin J,Wang Q,Chen X,et al.Sustained Release-Driven Formation of Ultrastable SEI between Li6PS5Cl and Lithium Anode forSulfide-Based Solid-State Batteries.Advanced Energy Materials 2021,11(4).
[0158] 6.Liang J,Li X,Zhao Y,Goncharova LV,Wang G,Adair KR,et al.In SituLi3PS4 Solid-State Electrolyte Protection Layers for Superior Long-Life andHigh-Rate Lithium-Metal Anodes.Advanced Materials 2018,30(45).
[0159] 7.Lee Y-G,Fujiki S,Jung C,Suzuki N,Yashiro N,Omoda R,et al.High-energy long-cycling all-solid-state lithium metal batteries enabled bysilver-carbon composite anodes.Nature Energy 2020,5(4):299-308.
[0160] 8.Tan DHS,Chen Y-T,Yang H,Bao W,Sreenarayanan B,Doux J-M,etal.Carbon-free high-loading silicon anodes enabled by sulfide solidelectrolytes.Science 2021,373(6562):1494.
[0161] 9.Lee K,Han S,Lee J,Lee S,Kim J,Ko Y,et al.Multifunctional Interfacefor High-Rate and Long-Durable Garnet-Type Solid Electrolyte in Lithium MetalBatteries.Acs Energy Letters 2022,7(1):381-389.
[0162] 10.Zhou L,Zuo T-T,Kwok CY,Kim SY,Assoud A,Zhang Q,et al.High arealcapacity,long cycle life 4 V ceramic all-solid-state Li-ion batteries enabledby chloride solid electrolytes.Nature Energy 2022,7(1):83-93.
Claims
1. A lithium metal-containing composite layer, characterized in that, The lithium-containing metal composite layer includes a lithium-containing layer, and an interface layer is disposed on the surface of the lithium-containing layer. The interface layer includes soft carbon, β-Li3N, and LiC6. The lithium-containing metal composite layer exhibits characteristic peaks at 23.6°, 32.1°, and 35.8° in its X-ray powder diffraction pattern, expressed as a diffraction angle of 2θ. The raw materials for the interface layer include soft carbon and Li3N; the mass ratio of soft carbon to Li3N is soft carbon:Li3N = 100% - X%:X% (0.5%). <X≤20)。 2. The lithium-metal composite layer according to claim 1, characterized in that, The lithium-containing layer contains metallic lithium.
3. The lithium-containing metal composite layer according to claim 1, characterized in that, The mass ratio of soft carbon to Li3N is soft carbon:Li3N=100%-X%:X% (7≤X≤13).
4. The lithium-metal composite layer according to claim 1, characterized in that, The soft carbon includes one or more of petroleum coke, needle coke, carbon fiber, coke, and carbon microspheres.
5. The lithium-metal composite layer according to claim 1, characterized in that, The raw materials for the interface layer also include adhesives.
6. The lithium-metal composite layer according to claim 5, characterized in that, The adhesive includes one or more of PTFE, polyvinylidene fluoride, styrene-butadiene rubber, alginate, polyacrylonitrile, and sodium carboxymethyl cellulose.
7. The lithium-containing metal composite layer according to claim 5, characterized in that, The amount of binder added is 4%-6% of the total mass of soft carbon and Li3N.
8. The lithium-metal composite layer according to claim 1, characterized in that, The thickness of the interface layer is 30μm-100μm.
9. A lithium-metal composite layer according to claim 1, characterized in that, The thickness of the interface layer is 30μm-50μm.
10. A method for preparing a lithium-containing metal composite layer according to any one of claims 1-9, characterized in that, The preparation method includes: mixing soft carbon and Li3N to form a precursor interface layer, combining the obtained precursor interface layer with a lithium-containing layer and subjecting it to pressure and heat preservation treatment to obtain a lithium-containing metal composite layer. The pressure per unit area of the pressurized area shall not be less than 875 MPa; The temperature of the heat preservation treatment is 45℃-65℃, and the heat preservation treatment time is 11h-13h.
11. The preparation method according to claim 10, characterized in that, The pressure per unit area of the pressurized area is 875MPa-1000MPa.
12. The preparation method according to claim 10, characterized in that, The preparation method further includes mixing soft carbon and Li3N and then adding a binder; The preparation method is characterized by an inert gas atmosphere.
13. The preparation method according to claim 12, characterized in that, The inert gas includes one of argon, nitrogen, helium, krypton, and xenon.
14. A negative electrode, positive electrode, or separator comprising a lithium metal composite layer as described in any one of claims 1-9 or a lithium metal composite layer prepared by the preparation method as described in any one of claims 10-13.
15. A battery comprising the negative electrode, positive electrode, or separator as described in claim 14.
16. An electrochemical device comprising the negative electrode, positive electrode, or separator as described in claim 14.
17. The battery according to claim 15, characterized in that, The battery includes a sulfide solid electrolyte battery or an all-solid-state lithium metal battery.
Citation Information
Patent Citations
Activated negative electrode with lithium dendrite inhibition effect
CN114899348A
Anode for lithium secondary battery, production method therefor, and lithium secondary battery comprising same
US20200075942A1